Improving emergency department overcrowding in Malaysian government hospital - Wan Malissa Wan Mohd Aminuddin,; Wan Rosmanira Ismail, (Penerbit Universiti Kebangsaan Malaysia, 2021)
There have been a marked increase in emergency department (ED) visits. This has led to healthcare problems in ED, particularly overcrowding. This paper aims to contribute towards ED overcrowding by increasing the efficiency level of the department through eliminating ED bottlenecks and reallocating ED resources. An ED located in Kuala Lumpur was chosen as the study setting. Integration of Discrete Event Simulation (DES) and Data Envelopment Analysis (DEA) were adopted in this study. DES is used to model the ED system and to identify the system bottlenecks. Meanwhile, DEA is applied to select the best alternative to resources allocation. We also present a novel mathematical equation for generating resources allocation alternatives based on the hospital budgets. The new configuration number of ED resources constructed in this study improved the system bottlenecks. Patients’ waiting time was reduced by 52%. The utilisation rate among Red Zone Doctors, Green Zone Doctors and Yellow Zone Nurses was reduced successfully from 89% to 85%, 98% to 90% and 91% to 89%, respectively. In conclusion, the finding in this study has produced better results in patient waiting time and resource utilisation and thus, enhance the hospital efficiency. Hopefully, in future the hospital will become a role model for other hospital in improving their services.